"Complicated Windings": "Mont Blanc". Issue 5 (3rd September 2022) - Hodgson, Andrew
ABSTRACT: "Mont Blanc" is a difficult and rewarding poem because its efforts to make sense of experience are paralleled by the challenges of interpretation which it affords the reader. Shelley's confrontation with the Alpine landscape is shaded by ironies and counter-perspectives which frustrate any attempt to extract from the poem any stable vision of the mind's relation with the external "universe of things." "Mont Blanc" testifies to the power of the imagination through its very willingness to concede its weakness. The essay embarks on the apparently basic task of following the shifts in the poem's argument over its five numbered sections. It shows how sentences warp and drift under the influence of continually evolving ideas and impressions and suggests, at least implicitly, that the poem's force and depth owe to a subtlety of expression and imaginative flair which elude the generalizing tendency of critical interpretation.